ENURESIS IN ADOLESCENTS AND CONSCRIPTS: MODERN APPROACHES TO DIAGNOSTICS - A. L. Malykh; I. N. Zakharova; M. I. Pykov (Union of pediatricians of Russia, 2014)
The article lists results of a complex examination of adolescents and conscripts of 15-23 years of age with enuresis performed according to the Ulyanovsk Region military commissariat's referral in 2003-2012. The main methods of diagnostics were pelvic ultrasound, Doppler sonography of renal arteries, electric encephalography, uroflowmetry and sexual hormones level determination. Increase in size and volume of prostate gland, reduction in total testosterone and luteinizing hormone blood levels, high spread of vesicoptosis (prolapse of urinary bladder) and nephroptosis were revealed in 67.3 % of conscripts with nocturnal enuresis in comparison with healthy conscripts.